2020
DOI: 10.1002/ps.5896
|View full text |Cite
|
Sign up to set email alerts
|

Why don't smallholder farmers in Kenya use more biopesticides?

Abstract: Background: Although Kenya has a relatively high number of registered biopesticide products, little is known about biopesticide use by smallholders. This paper documents farmers' current use and perception of chemical pesticides and biopesticides, their willingness to pay for biopesticides, and the key challenges to biopesticide uptake. Results: A survey found that chemical pesticides are used widely by smallholders despite awareness of the risks to human health and the environment. Almost half of respondents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 26 publications
3
37
0
Order By: Relevance
“…The development of insecticide resistance is rapid and widespread and threatens crop productivity. In contrast, biopesticides (e.g., fungus and plant extracts) have therefore emerged as a better alternative for pest control [8][9][10]. They can potentially reduce the use of chemical pesticides and provide new ideas for the synthesis of novel biopesticides for pest control [8,9,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of insecticide resistance is rapid and widespread and threatens crop productivity. In contrast, biopesticides (e.g., fungus and plant extracts) have therefore emerged as a better alternative for pest control [8][9][10]. They can potentially reduce the use of chemical pesticides and provide new ideas for the synthesis of novel biopesticides for pest control [8,9,11].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, biopesticides (e.g., fungus and plant extracts) have therefore emerged as a better alternative for pest control [8][9][10]. They can potentially reduce the use of chemical pesticides and provide new ideas for the synthesis of novel biopesticides for pest control [8,9,11]. Some plant extracts are being used for the management of insect pests such as Plutella xylostella, and Drosophila suzukii, and their application is becoming an integral part of ecological conservation programs [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…A baseline survey of farmers in major citrus-producing counties of Kenya by Gitahi et al (2019) highlighted the lack of knowledge on alternative pest management practices other than pesticides. A study by Constantine et al (2020) also confirmed the low use of biopesticide products in Kenya, alongside high use of conventional chemical pesticides. In Africa, most farmers depend solely on the use of synthetic pesticides to minimize damage and output losses due to the citrus greening pest complex.…”
Section: Chemical Controlmentioning
confidence: 79%
“…Notwithstanding the injurious effects, the development of synthetic pesticides is a complex process and requires rigorous regulatory approval demands. Besides, they are often costly and beyond the reach of the resource-strained smallholder farmers that contribute immensely to global food security (Mburu et al, 2016;Constantine et al, 2020). In smallholder agroecosystems, pests and diseases cause agricultural losses ranging from 45 to 100% (McDonald and Stukenbrock, 2016), depending on the infestation level.…”
Section: Use Of Microorganisms In Suppression Of Pests and Diseasesmentioning
confidence: 99%